Coexistence of Autoimmune Encephalitis and Other Systemic Autoimmune Diseases - Zhao, Jing; Wang, Cancan; Xu, Xiaolu; Zhang, Yuanxing; Ren, Haitao; Ren, Zhixia; Li, Gai; Zhang, Jiewen; Guan, Hongzhi (Frontiers in Neurology, 2019)
Background: In recent years, the phenomenon of coexisting systemic autoimmune diseases (ADs) in patients with autoimmune encephalitis (AE) has been increasingly found, while its clinical significance remains unexplored. This study aimed to investigate the types and potential clinical associations of autoimmune comorbidities in patients with antibody-positive AE. Methods: A retrospective cohort study of patients with antibody-positive AE was conducted from 2011 to 2018. The demographics, clinical characteristics, and follow-up data were reviewed. Results: We enrolled 517 patients, among whom 45 were affected by one or more types of ADs, including Hashimoto's thyroiditis (HT) (n = 28), systemic lupus erythematosus (SLE) (n = 3), anaphylactoid purpura (n = 3), vitiligo (n = 3), Sjögren's syndrome (SS) (n = 2), chronic urticaria (n = 2), bullous pemphigoid (n = 1), uveitis (n = 1), myasthenia gravis (MG) (n = 1), and the coexistence of SLE and anaphylactoid purpura (n = 1). The proportion of patients with coexisting ADs was higher in those with anti–leucine-rich glioma-inactivated 1 (LGI1) encephalitis than in those with anti–N-methyl-d-aspartate receptor (NMDAR) encephalitis (13/111 vs. 16/307) (P = 0.021). In anti-NMDAR and anti-LGI1 encephalitis patients, there were no significant differences in the age at onset, sex ratio, proportion of patients with tumors, disease severity, or recurrence between the groups with and without ADs. Conclusions: One or more types of ADs developed in AE patients, and patients with anti-LGI1 encephalitis had a higher frequency of autoimmune comorbidities than those with anti-NMDAR encephalitis. And we found that autoimmune comorbidities did not affect the clinical course of AE.